Metabolic and Population Effects of Winter Tick Infestations on Moose: Unique Evolutionary Circumstances? - Pekins, Peter J. (Frontiers in Ecology and Evolution, 2020)
Moose (Alces alces) have evolved to store adequate body fat to emerge from winter in adequate nutritional condition that is key to annual productivity and neonatal survival. Blood consumption by winter ticks (Dermacentor albipictus) affects survival and productivity of moose, often resulting in marked local and regional die-offs of the calf segment of the population. Concurrent with an unprecedented frequency of winter tick epizootics (> 50% calf mortality) in the northeastern United States, productivity but not mortality of adult female moose has also declined due to low rates of twinning and calving. Chronic blood loss to winter ticks affects protein and energy balance in late winter-early spring when pregnant cows are in their energy- and protein-costly 3rd trimester, and will eventually calve and lactate initially in an environment low in digestible energy and protein. To describe this dynamic, I calculated the endogenous fat and protein balance of different-sized pregnant cows by developing energy balance equations that accounted temporally for gestation, winter tick infestation, and lactation under two consumption levels. The analysis revealed the critical importance of body mass and body fat as only large cows (25% pre-winter body fat) were immune from depletion of body fat at birth in all scenarios. Mid-sized cows (20% body fat) depleted fat reserves during gestation in most scenarios, and small cows (15% body fat) in all scenarios. The infestation and forage consumption levels influenced the predicted date of fat depletion up to several weeks, and failed calving or mortal mass loss associated with rapid loss of endogenous protein was possible in mid-sized and small cows. The continual decline in demographic parameters points to reduced body mass and body fat over time, or increased numbers of mid-sized and small cows in the population. Recent research is suggestive of a self-sustaining relationship largely influenced, ironically, by quality habitat and patterns of habitat use. This regional population is confronted with a unique and sustained combination of environmental and parasitic conditions associated with a warming climate that markedly affects its survival and reproduction in quality habitat, a unique occurrence in their evolutionary history.